From Exegesis to Exposition : A practical guide to using Biblical Hebrew - Chisholm Jr., Robert B. (Baker Books, 1999)
Inspires and instructs students and pastors to use the Hebrew Bible appropriately in their preaching and teaching. Includes sample sermons and lessons.